Chemical composition and larvicidal activity of the essential oil of Cymbopogon nardus (L.) Rendle on Anopheles gambiae. - GBAGUIDI, A. (My University, 2019)
The increasing resistance toward a number of insecticides of synthetic origin developed by Anopheles gambiae (the main vector of malaria in Benin) has prompted us to seek new pesticide formulations in the fight against malaria. In this study, we tested the insecticidal potential of the essential oil of Cymbopogon nardus on Anopheles gambiae larvae for two genotypes: the sensitive strain Kisumu of Kenyan origin and the wild strain from stagnant water in Cotonou. The essential oil of this plant obtained by steam distillation with a yield of 1.3 ± 0.11% was analyzed by chromatographic method (GC / MS). The main oil compounds were citronellal (37.87%), nerol (19.88%), citronellol (9.11%), elemol (7.40%) and gamma murollene (4.65%). Sensitivity tests performed on Anopheles gambiae larvae 3rd instar revealed the larvicidal properties of the oil tested. The lethal concentrations (LC50) figures obtained were respectively 36.83 ppm and 97.33 ppm for the Kisumu strain and the local wild population respectively. The LC90 adopted the same trend with 55.72 ppm and 147.9 ppm respectively for sensitive and wild larvae. The essential oil of Cymbopogon nardus constitutes thus a bioactive substance for a preventive strategy against malaria vectors by means of green chemistry.
Keywords: Anopheles gambiae; Cymbopogon nardus; Essential oil; Larvicidal activity.